Electromechanically Active As‐Electrospun Polystyrene Fiber Mat: Significantly High Quasistatic/Dynamic Electromechanical Response and Theoretical Modeling. Issue 14 (20th July 2020) - Ishii, Yuya; Yousry, Yasmin Mohamed; Nobeshima, Taiki; Iumsrivun, Chonthicha; Sakai, Heisuke; Uemura, Sei; Ramakrishna, Seeram; Yao, Kui
Abstract : Front Cover : In article 2000218, Yuya Ishii and co‐workers demonstrate the large quasistatic/dynamic electromechanical response of as‐electrospun fiber mats composed of a commodity polymer, atactic polystyrene. These fiber mats could pave the way for the development of low‐cost/large‐area, flexible, and lightweight pressure sensors as well as actuators.